2002
DOI: 10.1029/2001gl014320
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic opal indicating less productive northwestern North Pacific during the glacial ages

Abstract: Biogenic opal and ice‐rafted detritus (IRD) data from sediments in the Okhotsk Sea and the neighboring North Pacific revealed the remarkable reduction in opal production and southward advancement of sea‐ice covered area during the last glacial maximum, resulting also southward shift of high biological productive area in the northwestern North Pacific. It implies that the substantial reduction in outflux of CO2 to the atmosphere in northwestern North Pacific and the pronounced increase in CO2 sequestering in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 22 publications
(26 reference statements)
8
39
0
Order By: Relevance
“…Higher opal content during the deglaciation than in the other periods after LGM in the NW Pacific and its marginal seas was reported . The period of high opal content indicated by Narita et al (2002) was the same as those of high water content horizons in our results. Thus, high water content might relate to diatom productivity in surface water.…”
Section: Core Correlation and Temporal Change Of Sediment Lithology Asupporting
confidence: 70%
See 1 more Smart Citation
“…Higher opal content during the deglaciation than in the other periods after LGM in the NW Pacific and its marginal seas was reported . The period of high opal content indicated by Narita et al (2002) was the same as those of high water content horizons in our results. Thus, high water content might relate to diatom productivity in surface water.…”
Section: Core Correlation and Temporal Change Of Sediment Lithology Asupporting
confidence: 70%
“…Harada et al (2004) indicated the change of surface circulation in the North Pacific between LGM and Holocene. Narita et al (2002) reported lower biogenic opal production, indicating less atmospheric carbon fixation, during LGM. Therefore, paleoceanographic studies in the source region of the NPIW are very important to understand modern and ancient carbon cycling in the global ocean.…”
Section: Introductionmentioning
confidence: 95%
“…1) Cook et al 2005;Gorbarenko et al 2005Gorbarenko et al , 2010Okazaki et al 2005;Tanaka and Takahashi 2005;Brunelle et al 2007;Itaki et al 2009;Caissie et al 2010). Narita et al (2002) also revealed a remarkable reduction in opal production due to the southward advancement of sea-ice cover in the northwestern Pacific during the last glacial period. By contrast, paleoproductivity was enhanced during the last deglaciation, showing distinct peak events of opal and carbonate production in the Bering Sea (Cook et al 2005;Gorbarenko et al 2005Gorbarenko et al , 2010Okazaki et al 2005;Brunelle et al 2007;Itaki et al 2009;Caissie et al 2010).…”
Section: Discussionmentioning
confidence: 87%
“…Major reorganization of ocean circulation in the North Pacific during the glacial-deglacial period affected productivity through upwelling. During the last glacial maximum, primary productivity in the subarctic Pacific was low because of stratification (Narita et al, 2002;Jaccard et al, 2005;Galbraith et al, 2007;Brunelle et al, 2010). Thick GNPIW with low nutrient concentrations down to ∼2000 m suppressed biological productivity in the euphotic layer.…”
Section: Implications For the Release Of Old Carbon From The Deep Seamentioning
confidence: 99%